IMPLEMENTASI METODE FUZZY TAHANI DALAM MENENTUKAN REKOMENDASI PEMBELIAN LAPTOP (Studi kasus di Toko Mega Alvindo Kalijati Subang) - Yuli Murdianingsih; Isti Isbahatunnisa (STMIK SUBANG, 2020)
Possible customers for laptops come from various walks of life. There are definitely laypeople whoalso understand from the context such as the history of IT education, and so on. To help providerecommendations in the purchasing of laptops, especially with variable type laptops, displayscreen widths, prices, memory capacity and hard disk capacity, a decision-based system isrequired where the machine uses the fuzzy tahini process. The case study was performed at theKalijati Subang district store in Mega Alvindo. 10 Laptop data records were selected andmembership functions for the laptop type variable, screen width, price, memory capacity, and harddisk capacity were created. Having reached the degree of variables. The recommendation systemis further developed through the design and implementation of a database, the design andimplementation of a web-based interface. A laptop purchasing recommendation system can beimplemented using the Fuzzy Resistant method with variable type laptops, monitor screen width,price, memory capacity and hard disk capacity.